Feed intake, nutrient utilization and microbial protein production in local male lambs fed noni seed (Morinda Citrifolia) - Karim, Muhammad Hesa; Muttaqien, Yudho Harbowo; Restitrisnani, Vita; Purbowati, Endang; Adiwinarti, Retno; Purnomoadi, Agung; Rianto, Edy (Journal of Advanced Veterinary Research, 2026)
A study was carried out to investigate the utilization of dietary protein in lambs fed a diet supplemented with noni seeds (Morinda citrifolia). This study used 20 male lambs (aged 4 months and weighing 12±1.36 kg) kept for 150 days. The lambs were allocated into a completely randomized design with 4 treatments of diet and 5 replications. The treatments were T0 (100% basal diet); T1 (90% basal diet + 10% noni seeds); T2 (80% basal diet + 20% noni seeds); T3 (70% basal diet + 30% noni seeds). The diet and drinking water were given ad libitum. The parameters measured were dry matter intake (DMI), dry matter digestibility (DMD), protein intake, protein digestibility, protein retention, Microbial Protein Production (MSP) and average daily gain (ADG). The results showed that inclusion of noni seed into the diet did not significantly affect (P>0.05) DMI (averaged 798.03 g/day), DMD (averaged 52.1%), protein intake (98.09 g/day), protein digestibility (averaged 74.88%), protein retention (averaged 73 %) and ADG (averaged 61.9 g/day). However, the treatments had a significant effect (P<0.05) on MSP; the lambs of T3 had the highest MSP (26 g/day) than those of T0, T1, and T2. The lambs of T0, T1, and T2 had no significant difference in MSP (averaged 17.5 g/day). In conclusion, the inclusion of noni seeds up to 30% into the diet improved Microbial Protein Production without a negative effect on protein utilization and lamb production. Therefore, the noni seed could be used as an alternative feedstuff for lambs.